Economics, politics, and administration in government lending ; the Regional Loans Boards of Nigeria - Schatz, Sayre P.; Nigerian Institute of Social and Economic Research (Ibadan : Published for the Nigerian Institute of Social and Economic Research [by] Oxford University Press, 1970)
This book appraises the performance of the Regional Loans Boards in discharging their function of promoting economic development through loans to indigenous private enterprise. The problems affecting the board operations like political manipulation, administrative inadequacy, and a want of buoyancy in the indigenous private sector of the economy were discussed.
Includes bibliographical references.
usc 17/05/2017
Loans